(untitled) (Tzintzun, Revista de Estudios Históricos, 2023)
This article studies the link of the Iquichanos with the viceregal administration, their participation in the process of the Independence of Peru and the reasons for the prolonging of the Iquichan rebellion. From the analysis of unpublished sources, we consider that the Iquichanos identified with the Spanish crown in exchange for having certain privileges. During the Independence they defeated the Cuzco rebellion of 1814 and harassed Sucre’s forces. Towards the first years of the republican government, they led a rebellion not only for economic reasons, but also because they were affected by the jurisdictional reorganizations and the prohibition of their cultural expressions.